Effect of different types of mulches on growth, yield and quality of okra (Abelmoschus esculentus) cv. GAO-5 (Current Horticulture, 2024)
The experiment was conducted in summer season 2017 at Agriculture Experimental Station, NAU, Paria (Gujarat) to assess the effect of different types of mulches on growth, yield and quality parameters of okra [Abelmoschus esculentus (L.) Moench] cv. GAO-5. The growth, yield and quality were studied under inorganic and organic mulch and compared with the control. The experiment was laid out in a randomized block design with three replications and nine treatments. The results reveled that among all the treatments silver polythene mulch: 50 micron showed significantly highest germination per cent (89.87%), number of branches/plant (3.13), plant height at final picking (114.93 cm), total dry biomass of plant (123.97 g/plant), marketable pod length (11.01 cm), number of pods/plant (15.15), pod weight (12.30 g), pod yield (0.188 kg/plant and 13.81 t/ha). The minimum days required for 50% flowering (37.00 days) and first picking (42.00 days) were noted under silver polythene mulch: 50 micron. The quality parameter such as ascorbic acid (mg/100g) and fibre content (%) were found non significant by different mulching treatments.
Keywords: Growth; Yield; Quality; Mulch; Summer season; Plant height; Germination